THE INFLUENCE OF BRAND MANAGEMENT AND ENTPRENEURSHIP MOTIVATION ON FRANCHISING SALES PERFORMANCE FRANCHISE COMPANY IN MANADO - Kumaat, Anastasia Eilin (Universitas Sam Ratulangi, 2015)
Flow economy today many franchise systems leads to large company tends to choose a franchise system than opening a new branch. Franchising done to overcome internal resources by providing access to the franchisee. With this tangle franchising develops and evolves. This research aim to improve the quality of business relationship, because franchising is built on the concept of the brand first and the effectiveness of consumer demand. The method used in this research is quantitative data; Quantitative data is concerned with testing hypotheses derived from theory and/or being able to estimate the size of a phenomenon of interest.Â Depending on the research question, participants may be randomly assigned to different treatments. If this is not feasible, the researcher may collect data on participant and situational characteristics in order to statistically control for their influence on the dependent, or outcome, variable. In business franchisee, the brand is the main reason for running a franchise business because the brand is an investment that is longer and an intangible asset that has a high equity brand management still needs to be maintained through. For the company management, in the franchise business, to improve the quality of business relationÂships need to pay more attention to brand management, because it has the greatest influÂence in maintaining the quality of the franchisee relationship. Keywords:brand management, enterpreneurship, motivation, franchising, sales.